Judicial Review by the Constitutional Court: A Democratic Oversight Instrument in Indonesia - Ernawati Huroiroh; Dossy Iskandar Prasetyo; Vera Rimbawani Sushanty (jfpublisher, 2026)
Judicial review is one of the constitutional authorities of the Constitutional Court that plays a central role in upholding constitutional supremacy, sustaining checks and balances, and strengthening constitutional democracy in Indonesia. This study examines the constitutional position and authority of judicial review exercised by the Constitutional Court within Indonesia's system of governance and assesses the implications of its judicial review decisions for the protection of citizens' constitutional rights within Indonesia's democratic system. The study employed normative legal research using statute, conceptual, and case approaches, drawing on primary, secondary, and tertiary legal materials analyzed qualitatively through a descriptive-analytical method. The findings show that the Constitutional Court holds a strategic position as guardian of the constitution, exercising authority to test statutes against the 1945 Constitution to ensure that legislative products remain consistent with the principles of the rule of law and constitutional democracy. This authority functions as an instrument of democratic oversight that restrains the misuse of legislative power and sustains institutional equilibrium. In addition, the Court's judicial review decisions carry significant implications for the protection of citizens' constitutional rights: through its authority to invalidate unconstitutional norms, the Court reinforces constitutional supremacy, increases the accountability of law-makers, and advances a constitutional democracy in which the constitution serves as the foundation of state power. Judicial review therefore functions not merely as a mechanism for testing legal norms but as a substantive instrument for strengthening democracy and protecting citizens' constitutional rights in Indonesia.